2021
DOI: 10.3389/fcell.2021.753004
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Oxidative Phosphorylation-Related and Immune Microenvironment Prognostic Signature in Uterine Corpus Endometrial Carcinoma

Abstract: Background: As the fourth most common malignant tumors in women, uterine corpus endometrial carcinoma (UCEC) requires novel and reliable biomarkers for prognosis prediction to improve the overall survival. Oxidative phosphorylation (OXPHOS) is found to be strongly correlated with the progression of tumor. Here, we aimed to construct an OXPHOS-related and immune microenvironment prognostic signature to stratify UCEC patients for optimization of treatment strategies.Method: Prognosis-associated OXPHOS-related di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 63 publications
1
9
0
Order By: Relevance
“…Furthermore, we validated the performance differences between our signature and other previously reported gene signatures in EC. The AUC of present protein signature for 1, 3 and 5 year OS prediction was higher in comparison with Hu's signature [ 23 ], Huang's signature [ 24 ], Liu's signature [ 25 ] and Qin's signature [ 26 ] (Fig. S 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we validated the performance differences between our signature and other previously reported gene signatures in EC. The AUC of present protein signature for 1, 3 and 5 year OS prediction was higher in comparison with Hu's signature [ 23 ], Huang's signature [ 24 ], Liu's signature [ 25 ] and Qin's signature [ 26 ] (Fig. S 3 a).…”
Section: Resultsmentioning
confidence: 99%
“…6 M). Studies have demonstrated the ability of IPS to predict the immunotherapy response of patients with colon cancer and uterine corpus endometrial carcinoma [ 30 , 46 ]. Thus, differences in IPS were assessed between HHSG and LHSG.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 289 OXPHOS-related genes (ORGs) were obtained by searching published studies [ 26 , 27 ]. Differentially expressed genes (DEGs) in the TCGA-COAD dataset were screened using the “limma” package [ 29 ].…”
Section: Methodsmentioning
confidence: 99%
“…With the advancement in next-generation sequencing technology, OXPHOS has been reported to be used in risk prediction models for lung adenocarcinoma and uterine corpus endometrial carcinoma [ 26 , 27 ]. Therefore, we aim to identify ORGs as prognostic markers of COAD and a risk score signature of ORGs was then established and validated to provide possible guidance for immunotherapy in COAD patients.…”
Section: Introductionmentioning
confidence: 99%